Interaction and its role in English (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Communicating clearly is important whether you are communicating with your boss, a colleague, a teacher, or a personal friend. Unclear, vague communication or communicating only some of the information needed can lead to misunderstandings or worse. When communicating in writing, it is important to remember some basic communication guidelines to ensure that you provide all the information needed in an appropriate manner, thus avoiding problems in the future.